Developments of Oil Stocks and their Impact on Oil Prices in the Global Energy Markets - Al-Yasiri, Ahmed Jassim; Ali, Maan Abood; Ali, Raed Saiad; K, Hasan Latif; Bekheet, Heider Nima (International Journal of Psychosocial Rehabilitation, 2020)
Oil stocks have been characterized by many changes during the last two decades. These changes are resulting from changes in prices on the one hand and economic fluctuations on the other hand. This study, therefore, seeks to identify the most important types of oil stocks, as well as developments in the size of these stocks, and then its impact on global oil prices. Besides, the role of these stocks in stabilizing the global oil market will be touched upon..